Bottom Drag Variations Under Waves and Currents: A Case Study on a Muddy Deposit off the Shandong Peninsula - Qi, Fukang; Liu, Zhiqiang; Xu, Jingping (Frontiers in Earth Science, 2022)
Bottom drag coefficient is one of key parameters in quantifying shelf hydrodynamics and sediment transport processes. Bottom drag coefficient varies markedly due to dynamic forcing and bed type differences, so a set of empirical values have been used for beds of coarse material where bedforms are often present. In comparison, dramatically fewer such rule-of-thumb values are available for muddy beds. Here we present results of variations in bottom drag as calculated from in situ measurements by bottom mounted tripods that were placed across the top of a muddy deposit during two different deployments, one in summer and another in winter. A tidal asymmetry of bottom drag was observed, most likely caused by variations of local bed roughness. For hydrodynamically smooth (Re<2.3×10^5) flows, computed values of bottom drag coefficient were fairly scattered but still showed an overall decreasing trend with an increase of Reynolds number. The bottom drag coefficient for hydrodynamically rough or transitional flow was typically constants, while the averaged drag coefficient over all observation periods was 1.7×10^(-3). Smaller waves (bottom orbital velocity ub<0.1 m/s), had a very limited impact on bottom drag coefficient. However, with an increasing ub, the wave-current interactions can decrease the time-averaged near-bed velocity and enhance turbulent kinetic energy, thus leading to an increase in the drag coefficient.